Vpliv gibalnih programov Specialne olimpiade Slovenije na izboljšanje gibljivosti ramenskega obroča odraslih oseb z intelektualno motnjo - Kovačič, Tine (Šport (Ljubljana), 2019)
A modern society faces the challenge of providing vulnerable groups of adults with intellectual disabilities in the aging process with appropriate support in improving physical fitness and an active lifestyle. In the study we used the integration of a quantitative (randomized clinical study) and a qualitative (phenomenological study) research methodology in order to study the shortterm effectiveness of the three different Special Olympics programs of physical activity on flexibility in the shoulder joint and to qualitatively study the improvement in this case in athletes with intellectual disability.
Keywords: athletes with intellectual disability; functional shoulder rotation; funkcionalna ramenska rotacija; physical fitness; Special Olympics; Specialna olimpiada; športniki z intelektualno motnjo; telesna pripravljenost